Professional Whats App Blast: Best practice direct digital marketing 4.0 to improve students’ religious moderation implementation - Permadi, Rudi; Zaenudin, Udin (Research and Social Study Institute, 2025)
There were no final literatures both national and international research concerning direct digital marketing of religious moderation using application. One of the solutions for direct digital marketing of religious moderation is using professional Whats App Blast. The study was conducted to determine the effect of professional Whats App Blast to improve the implementation of religious moderation. Mixed method acts as a method in this research. Data collection techniques using tests and interviews. The number of sample is 150 students from three campuses in West Java Province. Random sampling technique was used as a sampling technique. The calculation of data analysis shows that Asymp. Sig. (2-tailed) =0.000 less than Asymp. Sig. (2-tailed) <0.05 which means H0 is rejected. The results of the data analysis are reinforced by the calculation of the average value after the post test is higher than the pre test. The average student pre test is 52.53, while the average student after post test is 74.77. In addition, the author took other strength data from interviews. In conclusion, Professional Whats App Blast has a very positive contribution in improving the implementation of religious moderation of students in West Java Province. The next researcher is recommended to use other social media platforms besides Professional WA Blast and also the religious moderation information content is not limited to flyers.